Spiral and conformal cooling in plastic injection molding. (June 2015) - Wang, Yu; Yu, Kai-Min; Wang, Charlie C.L.
Abstract: Designing cooling channels for the thermoplastic injection process is a very important step in mold design. A conformal cooling channel can significantly improve the efficiency and the quality of production in plastic injection molding. This paper introduces an approach to generate spiral channels for conformal cooling. The cooling channels designed by our algorithms has very simple connectivity and can achieve effective conformal cooling for the models with complex shapes. The axial curves of cooling channels are constructed on a free-form surface conformal to the mold surface. With the help of boundary-distance maps, algorithms are investigated to generate evenly distributed spiral curves on the surface. The cooling channels derived from these spiral curves are conformal to the plastic part and introduce nearly no reduction at the rate of coolant flow. Therefore, the channels are able to achieve uniform mold cooling. Moreover, by having simple connectivity, these spiral channels can be fabricated by copper duct bending instead of expensive selective laser sintering. Highlights: Spiral conformal cooling channels with high speed coolants. An efficient algorithm to generate smooth spiral curves on free-form surfaces. Spiral curves are governed by an approximated boundary-distance-map (BDM). Region decomposition for covering by contours of BDM.